Albright the Beautician Reveals Secrets of Queen Esther's Cosmetic Aids (The Biblical archaeology review, 1976)
After Esther, ward of Mordecai, entered the harem of the Persian king Ahasuerus, she, along with the other virgins from whom the King would choose his queen, underwent a year’s preparation before being taken to the King. The Bible tells us that: